Lexical Verbs in Lithuanian Spoken Academic Discourse: Hedging in Lecturers’ Speech in Humanities and Social Sciences - Maslauskienė, Greta (Lietuvių kalba, 2024)
This study investigates the use of lexical verbs as hedging devices in Lithuanian academic discourse, based on data from the VuSemCorp corpus, which comprises seminar texts from the humanities (philosophy, literature, linguistics) and social sciences (sociology, political science, communication studies). The analysis focuses on the frequency, semantic categories, and pragmatic functions of lexical verbs in lecturers’ speech. Findings reveal that lecturers strategically employ lexical verbs to acknowledge alternative interpretations, soften criticism and directives, and demonstrate politeness. Hedging their utterances enables lecturers to adopt the role of guides or facilitators rather than authoritarian figures, thereby cultivating an open, interactive, and collaborative learning environment.An interdisciplinary perspective highlights that the use of lexical verbs for hedging varies by discipline. Sociology, linguistics, and philosophy demonstrated the highest frequency and diversity of hedging verbs. Lecturers in these fields showed a pronounced tendency to soften statements using first-person singular and plural forms, marking their subjective opinions and sharing interpretative responsibility with students. This linguistic strategy reflects a stronger emphasis on engaging students in co-constructing knowledge specific to these disciplines.Additionally, this article emphasizes the roles of (inter)subjectivity, politeness, and speaker commitment in the relatively understudied domain of Lithuanian spoken academic discourse. These findings contribute to a deeper understanding of how hedging shapes communication dynamics in academic settings.
Keywords: hedges; speaker stance; lexical verbs; spoken academic discourse; interdisciplinary perspective